Can Tele-Health Support Self-Care and Empowerment? A Qualitative Study of Hip Fracture Patients' Experiences With Testing an "App" - Charlotte M. Jensen PhD; Soren Overgaard PhD; Uffe Kock Wiil PhD; Jane Clemensen PhD (SAGE Publishing, 2019)
Telemedicine or tele-health is increasingly used to help meet challenges in health care linked to demographic changes and an aging population. This study aimed to investigate whether a tele-health solution, an "app" presented on a tablet, can assist patients in their recovery following a hip fracture and accommodate individual learning and health literacy needs to support them in self-care and empowerment. Twenty patients with a hip fracture were informed and educated using an app during hospital admission and for 3 to 4 weeks after discharge. A qualitative approach employed field observation and individual interviews with patients and their relatives. Data were analyzed using qualitative content analysis. Patients found that the app supported their ability to perform self-care and their desire for autonomy. They would not have downloaded the app by themselves but found the use of the app presented on a tablet very supportive in their everyday life while rehabilitating after a hip fracture. Findings indicate that health-care professionals can support information and education for patients with a hip fracture using an app that accommodates different learning styles. This demonstrates that apps used for the dissemination of health knowledge can be used by elderly hip fracture patients even if they are not used to technology.